A closer look at the creativity gap and why students are less creative at school than outside of school. (June 2017) - Runco, Mark A.; Acar, Selcuk; Cayirdag, Nur
Highlights: The present investigation explored creativity gap, which is the discrepancy between creativity demonstrated in versus outside of the school. Significantly more creativity was reported in the activities occurring outside compared to in school. Students' social preferences, creative attitudes and values, and creative personality traits explained much of the creativity gap. The results imply that the structure of schools is not compatible with some of what is required for creativity, such as autonomy and independence. Abstract: Previous research has reported that there is a discrepancy between the creativity students display when they are in school and that which they display when they are not in school. The present investigation explored this creativity gap . A measure that captures creative activity and achievement in various domains (art, science and technology, everyday creativity) was administered to 254 Turkish undergraduates. This investigation also used statistical techniques that allowed the explanatory power of personality, creative attitudes and values, students' perceptions of supports and barriers at school, and various background variables, such as parental education to be determined. Results confirmed that there was a discrepancy between the in school and outside of school creative activities and achievements. Significantly more creativity was reportedly displayed outside rather than in school. Students' social preferences, creative attitudes and values, and creative personality traits explained much of the discrepancy. Various interpretations of these results are examined, one being that students have creative potential, as evidenced by their creative activities and achievements outside of school, but these potentials are not displayed when they are in school, perhaps because usually there is more structure and more restrictions in school, and creativity entails autonomy and independence. Limitations and future research are discussed.